Penerapan Pembelajaran Berbasis ADLX Terpadu Berdiferensiasi untuk Meningkatkan Hasil Belajar Algoritma Pemrograman Scratch Siswa - Diyanah, Rif'atud; Kusumawati, Endah Tri; Lestari, Yayuk Sri (PTK: Jurnal Tindakan Kelas, 2024)
This research is motivated by the diversity of student abilities and the material being studied requires strong logical skills as well as the ability to sequence cause and effect which is manifested in certain rules so that it makes student learning outcomes different. Students with low abilities tend to be left behind and students with high abilities will get bored quickly. The purpose of this study is to improve the learning outcomes of Scratch Programming Algorithm material in class VII students of SMPIT Al Uswah Tuban. This research method uses classroom action research. The research stages consist of two cycles. Each cycle consists of four steps: planning, action, observation, and reflection. Data collection techniques with quantitative data from student learning outcomes in each cycle in the form of average student learning outcomes per cycle, the difference in student scores between the learning outcomes of prerequisite material and cycle 1, and the difference in learning outcomes of cycle 1 and cycle 2. For qualitative data, it is done by analyzing observation sheets. From this study, the average student learning outcomes increased from 71.88 (pre-cycle) to 82.76 (cycle 1) and 86.16 (cycle 2). Individually, in cycle 1, 84% of students showed an increase in learning outcomes while 16% of students showed a decrease. In cycle 2, 64% of students showed an increase and 36% showed a decrease. From these data, it can be concluded that there is an increase in learning outcomes with the implementation of Integrated ADLX learning on the Scratch Programming Algorithm material.